Interoperability, switchability and portability: Implications for the cloud - Ilsa Godlovitch; Peter Kroon (WIK-Consult GmbH, 2022)
Cloud computing is an important enabler for the digital economy. In addition to reducing costs, cloud computing can improve access to advanced IT solutions, boosting innovation and productivity across a wide range of sectors. As cloud computing has gained momentum, there has been an increasing focus on the need to ensure that customers can make use of multiple services and are not locked into their cloud provider(s). The concepts of interoperability and portability are not new, even in the emerging cloud computing ecosystem, and have been well-described through ISO/IEC standards. Furthermore there are well-established examples of regulatory requirements relating to interoperability and portability in other sectors, notably telecoms and banking, as well as interoperable services that have emerged "by design" such as email. However, the application of regulatory requirements on interoperability and portability to the cloud requires further analysis as the services and possible scenarios for interoperability and porting are significantly more complex than in the cases where these concepts have been mandated in the past and the problems, causes and implications of specific solutions to address lock-in concerns linked to cloud computing (including unintended consequences) may not have been adequately described. This study seeks to provide guidance on what is meant by cloud computing services, and what is meant by interoperability and portability. We describe how these concepts have been applied in other sectors, in which circumstances they may be relevant to cloud computing, the benefits and risks (including potential implications for differentiation and innovation) and what might be the implications for the ongoing review of the Data Act. – – Cloud Computing ist ein wichtiger Enabler für die digitale Wirtschaft. Cloud Computing kann nicht nur Kosten senken, sondern auch den Zugang zu fortschrittlichen IT-Lösungen verbessern und Innovation und Produktivität in einer Vielzahl von Sektoren fördern. Da Cloud Computing an Dynamik gewonnen hat, konzentriert man sich zunehmend auf die Notwendigkeit, sicherzustellen, dass Kunden mehrere Dienste nutzen können und nicht an ihren Cloud-Anbieter gebunden sind. Die Konzepte der Interoperabilität und Portabilität sind nicht neu, auch nicht im sich entwickelnden Cloud-Computing-Ökosystem, und wurden durch ISO/IEC-Standards gut beschrieben. Darüber hinaus gibt es bewährte Beispiele für regulatorische Anforderungen in Bezug auf Interoperabilität und Portabilität in anderen Sektoren, insbesondere Telekommunikation und Bankwesen, sowie interoperable Dienste, die 'by design' entstanden sind, wie z. B. E-Mail. Die Anwendung regulatorischer Anforderungen an Interoperabilität und Portabilität auf die Cloud erfordert jedoch weitere Analysen, da die Dienste und möglichen Szenarien für Interoperabilität und Portierung wesentlich komplexer sind als in den Fällen, in denen diese Konzepte in der Vergangenheit vorgeschrieben wurden, und die Probleme, Ursachen und Auswirkungen spezifischer Lösungen zur Vermeidung von Lock-in-Problemen im Zusammenhang mit Cloud Computing (einschließlich unbeabsichtigter Folgen) möglicherweise nicht angemessen beschrieben worden sind. Diese Studie soll eine Orientierung darüber geben, was im Zusammenhang mit Cloud-Computing-Diensten unter Interoperabilität und Portabilität zu verstehen ist. Wir beschreiben, wie diese Konzepte in anderen Sektoren angewendet wurden, unter welchen Umständen sie für Cloud Computing relevant sein könnten, welche Vorteile und Risiken (einschließlich möglicher Implikationen für Differenzierung und Innovation) damit verbunden sind und welche Auswirkungen sich auf die laufende Überprüfung des Data Act ergeben könnten.
Additional information: Study for Microsoft
Keywords: 330; Cloud Computing; Interoperabilität; Software; EU-Staaten